2017
DOI: 10.1021/acs.analchem.6b03324
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analytical and Statistical Two-Dimensional Spectroscopy Strategy for Metabolite Identification: Application to Dietary Biomarkers

Abstract: A major purpose of exploratory metabolic profiling is for the identification of molecular species that are statistically associated with specific biological or medical outcomes; unfortunately, the structure elucidation process of unknowns is often a major bottleneck in this process. We present here new holistic strategies that combine different statistical spectroscopic and analytical techniques to improve and simplify the process of metabolite identification. We exemplify these strategies using study data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 42 publications
3
59
0
Order By: Relevance
“…cetoleic acid [25][26][27][28][29][30][31] Vegetables Vegetarian and lactovegetarian diet) Urine p-Hydroxyphenylacetate Hippurate; phenylacetylglutamine; lysine; hippurate; N-acetyl glycoprotein; succinate [19,32,33] Broccoli Urine Ascorbate; tetronic acids; l-xylonate/l-lyxonate; naringenin glucuronide [28] Onion Urine N-acetyl-S-(1Z)-propenyl-cysteine-sulfoxide 4-Ethyl-5-amino-pyrocatechol [34] Lettuce, spinach, green peppers Serum 3-Carboxy-4-methyl-5 -propyl-2-furanpropanoic [30] Cabbage, brussels sprouts, pointed cabbage Urine N-acetyl-S-(N-3-methylthiopropyl)cysteine; N-acetyl-S-(N-allylthiocarbamoyl)cysteine; iberin N-acetyl-cysteine; erucin N-acetyl-cysteine; N-acetyl-(N -benzylthiocarbamoyl)-cysteine; sulforaphane N-acetyl-cysteine; sulforaphane N-cysteine,3-Hydroxy-hippuric acid sulfate;…”
Section: Type Of Food Sample Type Candidate Biomarker Metabolitementioning
confidence: 99%
See 1 more Smart Citation
“…cetoleic acid [25][26][27][28][29][30][31] Vegetables Vegetarian and lactovegetarian diet) Urine p-Hydroxyphenylacetate Hippurate; phenylacetylglutamine; lysine; hippurate; N-acetyl glycoprotein; succinate [19,32,33] Broccoli Urine Ascorbate; tetronic acids; l-xylonate/l-lyxonate; naringenin glucuronide [28] Onion Urine N-acetyl-S-(1Z)-propenyl-cysteine-sulfoxide 4-Ethyl-5-amino-pyrocatechol [34] Lettuce, spinach, green peppers Serum 3-Carboxy-4-methyl-5 -propyl-2-furanpropanoic [30] Cabbage, brussels sprouts, pointed cabbage Urine N-acetyl-S-(N-3-methylthiopropyl)cysteine; N-acetyl-S-(N-allylthiocarbamoyl)cysteine; iberin N-acetyl-cysteine; erucin N-acetyl-cysteine; N-acetyl-(N -benzylthiocarbamoyl)-cysteine; sulforaphane N-acetyl-cysteine; sulforaphane N-cysteine,3-Hydroxy-hippuric acid sulfate;…”
Section: Type Of Food Sample Type Candidate Biomarker Metabolitementioning
confidence: 99%
“…3-hydroxy-hippuric acid; iberin N-acetyl-cysteine [29] Fruit Apples and pears Urine Phloretin [35,36]; rhamnitol [34] Citrus Urine Proline betaine; limonene 8,9-diol glucuronide; nootkatone 13,14-diol glucuronide; hesperetin 3 -O-glucuronide; hydroxyproline betaine; N-methyltyramine sulfate; naringenin 7-O-glucuronide; stachydrine; scyllo-and chiro-inositol [28,30,[35][36][37][38][39][40] Orange juice Urine N-methyl proline; methyl glucopyranoside (α+β); stachydrine; betonicine; N-acetyl putrescine; dihydroferulic acid [41] The identification of food biomarkers is an ongoing process; a consensus has not been reached as to which metabolites would be the most adequate biomarkers for different types of foods. Moreover, some metabolites are markers of categories of food, not being able to discriminate between the exact types of foods being analyzed (1-methylhistidine and 3-methylhistidine are found in meat and are not useful in discriminating between types of meat).…”
Section: Type Of Food Sample Type Candidate Biomarker Metabolitementioning
confidence: 99%
“…Previous literature has also identified biomarkers such as phloretin and rhamnitol as candidate biomarkers of apple intake. [ 31–34 ] Due to different study designs, analytical procedures, and apple variety it is not surprising to obtain different biomarkers. Previous work has demonstrated that rhamnitol levels in apples vary due to geographic location and highlights the need for validation of candidate biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31–33 ] The polyphenol epicatechin, its conjugates and metabolites, have also been associated with apple intake [ 31,33 ] but this polyphenol is commonly found in multiple foods. Many other compounds have been identified as potential markers of apple consumption, mainly in studies looking at consumption of multiple fruits, including rhamnitol [ 34 ] and metabolic products of quercetin. [ 32 ] While some interesting biomarkers for apple intake have emerged in the literature, it is clear that more work is needed in order to discover robust biomarkers of apple intake, and steps taken to validate these biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Within metabolic proling, 1 H Nuclear Magnetic Resonance (NMR) spectroscopy has become an extremely valuable tool for the characterisation of complex mixtures; 2 statistical spectroscopy tools have also been applied to extract information from complex spectral sets. 3 Posma et al 4 have demonstrated the use of statistical 2D NMR, utilising the RED-STORM probabilistic statistical spectroscopy tool on data acquired from diet-controlled human urine samples, in order to further expand the understanding of dietary biomarkers.…”
Section: Introductionmentioning
confidence: 99%